One of us is next - McManus, Karen M. (New York : Delacorte Press, 2020)
"A year after the Bayview four were cleared of Simon Kelleher's death, a new mystery has cropped up--a game with dangerous consequences that's targeting students at Bayview again. And if the creator isn't found soon, dangerous could prove deadly"--
HL740
Keywords: Detective and mystery stories; Gossip -- Fiction; High schools -- Fiction; Schools -- Fiction; Mystery and detective stories; Gossip -- Fiction; High schools -- Fiction; Schools -- Fiction